You can run : a novel - Cleveland, Karen (Ballantine Books, 2021)
"A CIA analyst makes a split-second decision that endangers her country but saves her son--and now she must team up with an answer-hungry journalist she's not sure she can trust in this electrifying thriller from the New York Times bestselling author of Need to Know. Nothing gets by Jill Bailey. As a CIA analyst, she's in charge of investigating and vetting new sources. Sources like FALCON, who's been on the fast-track to recruitment. He says he's a Syrian defense official attached to a covert biowarfare program--and with a global pandemic fresh in their minds, CIA officials are desperate to use him. It's Jill's job to make sure he is who he claims to be, and that his case officers in the field haven't been duped--or coerced. But before she can get to work, she gets a call. One that's every parent's nightmare. We have your son. And to get him back, Jill does something she thought she'd never do. As it turns out, she isn't the only one with questions about FALCON. Alex Charles, a journalist eager to break the next big story, begins to investigate an anonymous tip: an explosive claim about the CIA's hottest new source. This is the story that Alex has been waiting for. The tip--and a fierce determination to find the truth--leads Alex to Jill, who would rather remain hidden. As the two begin to work together, they uncover a vast conspiracy that will force them to confront their loyalties to family and country. You Can Run is an edge-of-your-seat thriller that will have you asking: What would you do to save the ones you love?"--